PENGARUH SIKLUS HIDUP PERUSAHAAN TERHADAP KEPEMILIKAN KAS PADA PERUSAHAAN YANG TERDAFTAR DI INDEKS KOMPAS 100 - Rahmawati, Fitri; Cahyo, Heru; Nirmala, Nirmala (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to determine the partial significance of the company's life cycle, leverage, profitability and company size on cash ownership of companies listed on the compass 100 index of the Indonesia Stock Exchange. The sampling method using purposive sampling obtained as many as 62 companies. The data analysis technique used is panel data regression. The results of data analysis show that the best model is the Fixed Effect Model with the results of the analysis of the expansion stage life cycle, stabilization stage life cycle and decline stage life cycle have a positive and significant effect on cash holdings. The implication of this research is that investors are expected to get an overview of the effect of the company's life cycle on the company's cash ownership policy. Companies in the stabilization stage have large cash holdings including for dividend payments, thus attracting the attention of investors to invest in these companies. By paying attention to the stages of the company's life cycle, it is hoped that it can minimize investor losses when investing and can provide maximum profit from investment. This research provides important understanding for company management in making decisions regarding cash allocation and risk management strategies. Keywords: Corporate Life Cycle, Cash Ownership